Study of the Legal Accountability System for Press Companies Based on the Press Law and the Criminal Code - Purnomo, Sagita; Rahman Maulana Siregar, Abdul; Ismaidar (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to examine the legal liability of media companies under the Press Law and the Criminal Code, as well as to analyse the obstacles and policies relating to the legal liability of media companies. The study employs a normative legal research design with a descriptive-analytical approach, discussing existing legal phenomena and issues and testing them against applicable legislation and legal norms. The results of this study indicate that the legal liability of press companies under Law No. 1 of 2023 on the Criminal Code is regulated in Articles 45 to 50 concerning the legal framework for corporations as subjects of criminal offences. Meanwhile, under Law No. 40 of 1999 on the Press, as set out in Articles 9, 12 and 18, it is stipulated that every press company in Indonesia must be a legal entity and must specify the name of the person in charge. Challenges regarding the legal liability of press companies stem from conflicts between legal norms, the attribution of fault, the large number of press companies that lack legal entity status, and the fact that corporations cannot be sentenced to imprisonment. Legal policies to address these challenges include: optimising inter-institutional cooperation and restorative justice, harmonising the application of additional penalties under the Criminal Code, and establishing standards for absolute editorial liability.